A pragmatic randomised multi-centre trial of multifamily and single family therapy for adolescent anorexia nervosa. Issue 1 (December 2016) - Eisler, Ivan; Simic, Mima; Hodsoll, John; Asen, Eia; Berelowitz, Mark; Connan, Frances; Ellis, Gladys; Hugo, Pippa; Schmidt, Ulrike; Treasure, Janet; Yi, Irene; Landau, Sabine
Abstract Background Considerable progress has been made in recent years in developing effective treatments for child and adolescent anorexia nervosa, with a general consensus in the field that eating disorders focussed family therapy (often referred to as Maudsley Family Therapy or Family Based Treatment) currently offers the most promising outcomes. Nevertheless, a significant number do not respond well and additional treatment developments are needed to improve outcomes. Multifamily therapy is a promising treatment that has attracted considerable interest and we report the results of the first randomised controlled trial of multifamily therapy for adolescent anorexia nervosa. Methods The study was a pragmatic multicentre randomised controlled superiority trial comparing two outpatient eating disorder focussed family interventions - multifamily therapy (MFT-AN) and single family therapy (FT-AN). A total of 169 adolescents with a DSM-IV diagnosis of anorexia nervosa or eating disorder not otherwise specified (restricting type) were randomised to the two treatments using computer generated blocks of random sizes to ensure balanced numbers in the trial arms. Independent assessors, blind to the allocation, completed evaluations at baseline, 3 months, 12 months (end of treatment) and 18 months. Results Both treatment groups showed clinically significant improvements with just under 60% achieving a good or intermediate outcome (on the Morgan-Russell scales) at the end of treatment in the FT-AN group and more than 75% in the MFT-AN group - a statistically significant benefit in favour of the multifamily intervention (OR = 2.55 95%; CI 1.17, 5.52;p  = 0.019). At follow-up (18 months post baseline) there was relatively little change compared to end of treatment although the difference in primary outcome between the treatments was no longer statistically significant. Clinically significant gains in weight were accompanied by improvements in mood and eating disorder psychopathology. Approximately half the patients in FT-AN and nearly 60% of those in MFT-AN had started menstruating. Conclusions This study confirms previous research findings demonstrating the effectiveness of eating disorder focused family therapy and highlights the additional benefits of bringing together groups of families that maximises the use of family resources and mutual support leading to improved outcomes. Trial Registration Current Controlled TrialsISRCTN11275465 ; Registered 29 January 2007 (retrospectively registered)